The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1098612x18806759
|View full text |Cite
|
Sign up to set email alerts
|

Tools for managing feline problem behaviors: Pheromone therapy

Abstract: Practical relevance: Cats are one of the most common companion animals in the world. However, relatively little scientific research has been conducted on cat behavior. With problem behaviors a leading reason for relinquishment of cats to shelters, or abandonment outdoors, solutions to address feline behavioral problems can have important welfare benefits. Because naturally occurring pheromones produce measurable species-specific responses in cats, the use of synthetic pheromone products consisting of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…With only two studies currently published, much remains to be learned about the efficacy of Feliway TM Felifriends in promoting amiable social behaviors, e.g., the settings for application and individual differences in their responses to the pheromone treatment. It has been suggested that kittens' early experience with the pheromone (hand-raised orphan vs. queen-raised) might influence their response to the appeasing pheromone (103). Cats under chronic stress show reduced behavioral diversity; therefore, promoting the expression of natural behavior (e.g., scratching) has welfare potential in stimulating behavioral diversity and reducing anxiety.…”
Section: Cat Scent Signature Mixtures and Pheromonementioning
confidence: 99%
“…With only two studies currently published, much remains to be learned about the efficacy of Feliway TM Felifriends in promoting amiable social behaviors, e.g., the settings for application and individual differences in their responses to the pheromone treatment. It has been suggested that kittens' early experience with the pheromone (hand-raised orphan vs. queen-raised) might influence their response to the appeasing pheromone (103). Cats under chronic stress show reduced behavioral diversity; therefore, promoting the expression of natural behavior (e.g., scratching) has welfare potential in stimulating behavioral diversity and reducing anxiety.…”
Section: Cat Scent Signature Mixtures and Pheromonementioning
confidence: 99%
“…The prevalence of different problem behaviours varies between study populations and methodologies [2], and the reasons for the problem behaviours are also diverse. Control of problem behaviours requires careful evaluation of the cat, its background and environment, along with an integrated approach to management that often includes the use of synthetic pheromones [4] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of patented synthetic pheromones have been developed for use in cats including a feline facial pheromone (FFP, specifically the F3 FFP fraction which is thought to be deposited in the environment during facial rubbing of objects and convey a sense of security and reduced stress), a cat appeasing pheromone (CAP-released by the queen during nursing and thought to enhance inter-cat bond formation and security), and a feline interdigital semiochemical (FIS-thought to be deposited on objects during environmental scratching behaviour) [9] [11] [19]. Since 1996, various commercial products have become available (respectively FELIWAY ® Classic, FELIWAY ® Friends, and Feliscratch ® , Ceva Santé Animale) based on these synthetic pheromones, and have been successfully used as an aid to managing stress (e.g., anxiety or frustration), intra-species conflict, and other undesirable behavioural problems [9] [11] [19].…”
Section: Introductionmentioning
confidence: 99%
“…Podemos encontrar no mercado três análogos sintéticos aos feromônios felinos, sendo que cada um possui apresentações e funções diferentes, como observado no Quadro 1 (Henzel & Ramos, 2018). Estes produzem respostas comportamentais espécie específicas, induzindo a uma resposta comportamental específica (Vitale, 2018). Quadro 1.…”
Section: Prevenção E Tratamentounclassified